Perceived exertion at different percents of the critical velocity in front crawl - Castro, F. A. S.; Franken, M.; Diefenthaeler, F. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of the present study was to compare and correlate the perceived exertion (PE) behaviour at different percents of the critical velocity (CV) in front crawl. Ten trained male swimmers (19.4 ± 2.2 years) performed five trials of 200 m at different percents of the CV (90, 95, 100, 103 and 105%), in random order, 90 s of passive rest. PE presented significant differences (p<0.05) among percents of the CV in front crawl. Significant correlation between PE with percents of the CV was observed (rho=0.785, p<0.01). Results suggest that PE increases as percent of the CV increase, but in a non-linear relationship.